Pemberdayaan Masyarakat Pesisir melalui Model Pengembangan Homestay Berbasis Sustainable Tourism di Pantai Wedi Awu Kabupaten Malang - Hapsari, Cecilia Indah; Permata, Bintang; Winarno, Agung; Hermawan, Agus (Jurnal Pengabdian Masyarakat, 2026)
This community service activity is motivated by the potential for homestay development in the coastal area of Wedi Awu Beach, Malang Regency, which has not been optimally managed within a sustainable tourism framework. The purpose of this study is to analyze and implement a sustainable tourism-based homestay development model to support coastal community empowerment. The method used is a participatory approach through Participatory Action Research (PAR), involving observation, interviews, and problem analysis with active participation from business actors and the local community. The results show that the implementation of the program through structured social media content planning and the development of “healing” and “beach vibes” branding concepts has improved business visibility and strengthened the homestay identity. In addition, this activity has enhanced managerial capacity, increased community involvement, and raised awareness of environmental sustainability. The resulting homestay development model reflects the integration of economic, social, and environmental aspects aligned with sustainable tourism principles. Therefore, this activity not only improves business competitiveness but also promotes sustainable coastal community empowerment.